2017
DOI: 10.1007/s00330-017-4854-4
|View full text |Cite
|
Sign up to set email alerts
|

Feature-tracking myocardial strain analysis in acute myocarditis: diagnostic value and association with myocardial oedema

Abstract: • Myocardial strain measures are considerably reduced in patients with suspected myocarditis. • Myocardial strain measures can sufficiently discriminate between diseased and healthy patients. • Myocardial strain measures show basic associations with the extent of myocardial oedema/inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
36
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 29 publications
10
36
3
Order By: Relevance
“…The main findings of our study are that (1) RV dysfunction may frequently be observed during the acute stage of myocarditis, (2) LV longitudinal strain was the only independent predictor of functional recovery upon follow-up. "Lake Louise" criteria CMR is increasingly used for the diagnosis, evaluation, and followup of patients suffering from myocarditis [7,8,13]. Using standard "Lake Louise" criteria, CMR can reliably detect inflammatory myocardial alteration in the acute setting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The main findings of our study are that (1) RV dysfunction may frequently be observed during the acute stage of myocarditis, (2) LV longitudinal strain was the only independent predictor of functional recovery upon follow-up. "Lake Louise" criteria CMR is increasingly used for the diagnosis, evaluation, and followup of patients suffering from myocarditis [7,8,13]. Using standard "Lake Louise" criteria, CMR can reliably detect inflammatory myocardial alteration in the acute setting.…”
Section: Discussionmentioning
confidence: 99%
“…Global systolic radial, circumferential and longitudinal strain and strain rate values were calculated from peak segmental data. Measurements were performed as previously described [13].…”
Section: Analysis Of Left and Right Ventricular Myocardial Strainmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, the introduction and coupling of the feature-tracking technique with MRI have allowed for the assessment of 3-D regional and global (longitudinal, circumferential, and radial strains) myocardial dysfunction ( 110 , 194 ). While FT MRI has become a popular choice in the clinic for assessment of myocardial strain ( 12 , 111 ), it is still in its infancy in animal models. Nonetheless, a recent study ( 99 ) evaluated FT MRI reproducibility in mice and reported good to excellent inter- and intraobserver reproducibility, suggesting that FT MRI shows analytic potential for experimental cardiac research.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%